Impact of TOF on Brain PET With Short-Lived 11C-Labeled Tracers Among Suspected Patients With AD/PD: Using Hybrid PET/MRI - Wimalarathne, D.D.N; Ruan, Weiwei; Sun, Xun; Liu, Fang; Gai, Yongkang; Liu, Qingyao; Hu, Fan; Lan, Xiaoli (Frontiers in Medicine, 2022)
Objective: To explore the impact of the TOF reconstruction on brain PET with short-lived 11C- labeled tracers in positron emission tomography magnetic resonance (PET/MR) brain images among suspected Alzheimer’s and Parkinson’s (AD/PD) patients. Methods: Patients who underwent 11C-CFT and 11C-PiB PET/MR imaging were retrospectively included in the study. Each PET LIST mode data was reconstructed with and without the TOF reconstruction algorithm. Standard uptake values (SUVs) of Caudate Nucleus (CN), Putamen (PU) and Whole-brain (WB) were measured. TOF and non-TOF SUVs were assessed by paired t-test. Standard formulas were applied to measure contrast, signal to noise ratio (SNR), and percentage relative average difference of SUVs (%RAD-SUVs). Results: Total 75 patients were included with the median age (years) and Body mass index (BMI-kg/m2) of 60.2±10.9 y and 23.9±3.7 kg/m2 in 11C-CFT (n=41) and 62.2±6.8 y and 24.7±2.9 kg/m2 in 11C-PiB (n=34), respectively. Higher average SUVs and positive %RAD-SUVs were observed in CN and PU in TOF compared to non-TOF reconstructions for the two 11C-labeled radiotracers. Differences of SUVmean were significant (P<0.05) in CN and PU for both 11C-labeled radiotracers. SUVmax was enhanced significantly in CN and PU for 11C-CFT and CN for 11C-PiB, but not in PU. Significant contrast enhancement was observed in PU for both 11C-labelled radiotracers, whereas SNR gain was significant in PU, only for 11C-PiB in TOF reconstruction. Conclusion: TOF leads to a better signal versus noise trade-off than non-TOF in 11C-labeled tracers among CN and PU, improving the SUVs, contrast and SNR, which was valuable for reducing injected radiation dose. Improved timing resolution aided the rapid decay rate of short-lived 11C-labeled tracers, and it shortened the scan time, increasing patient comfort and reducing motion artefact among AD/PD patients. However, one should adopt the combined TOF algorithm with caution for quantitative analysis because it has different effects on the SUVmax, contrast and SNR of different brain regions.